WHSC1/NSD2 regulates immune infiltration in prostate cancer. Issue 2 (15th February 2021) - Want, Muzamil Y; Tsuji, Takemasa; Singh, Prashant K; Thorne, James L; Matsuzaki, Junko; Karasik, Ellen; Gillard, Bryan; Cortes Gomez, Eduardo; Koya, Richard C.; Lugade, Amit; Odunsi, Kunle; Battaglia, Sebastiano
Abstract : Background: Immunotherapy in prostate cancer (PCa) lags behind the progresses obtained in other cancer types partially because of its limited immune infiltration. Tumor-resident immune cells have been detected in the prostate, but the regulatory mechanisms that govern tumor infiltration are still poorly understood. To address this gap, we investigated the role of Wolf-Hirschhorn syndrome candidate 1 (WHSC1), a histone methyltransferase enzyme that targets dimethyl and trimethyl H3K36. WHSC1 is known to promote malignant growth and progression in multiple tumors, but its role in the interface between PCa and immune system is unknown. Methods: RNA Sequencing (RNASeq) data from patients with PCa from The Cancer Genome Atlas (TCGA) were collected and divided into top/bottom 30% based on the expression of WHSC1 and disease-free survival was calculated. Publicly available chromatin immunoprecipitation (ChIPSeq) data were obtained from Cistrome and integrated with the available RNASeq data. RNASeq, ATACSeq and methylomic were analyzed using R Bioconductor packages comparing C42 cells with or without stable knockdown on WHSC1. Flow cytometry was used to measure Major Histocompatibility complex (MHC) levels, MHC-bound ovalbumin and tumor infiltration. C57B6 and NOD scid gamma (NSG) mice were subcutaneously grafted with TRansgenic Adenocarcinoma of the Mouse Prostate (TRAMP) C2 cells and treated with MCTP39 (10 mg/kg); tumor size was monitored over time and curves were compared using permutation analyses. All analyses used a significance threshold of 0.05. Results: Leveraging TCGA data, we demonstrated that elevated WHSC1 levels positively correlate with the presence of an immunosuppressive microenvironment. We validated those results in vitro, demonstrating that genetic and pharmacological inhibition of WHSC1 restores antigen presentation. This occurs via an elegant epigenetic regulation of gene expression at the chromatin and DNA methylation levels. In vivo studies in immunocompetent mice also show an increased frequency of CD8 + T cells in tumors from mice treated with WHSC1 inhibitor, supporting the hypothesis that the antitumor effect following WHSC1 inhibition requires a fully functional immune system. Conclusions: This study demonstrates a novel role for WHSC1 in defining immune infiltration in PCa, with significant future implications for the use of immunotherapies in prostate malignancies.